A new species of Aleuropleurocelus Drews and Sampson (Hemiptera: Aleyrodidae) on grass from Mexico - Sánchez-Flores, Oscar Angel; Carapia-Ruiz, Vicente Emilio; Castillo-Gutiérrez, Antonio (Revista Colombiana de Entomología, 2022)
A new species of whitefly, Aleuropleurocelus popocatepetl Carapia-Ruiz y San- chez-Flores sp. nov., is described from the State of Morelos, Mexico. It was collected on the leaves of the grass Dichanthelium dichotomum (L.) Gould (Poaceae) in Ocuituco, Morelos. Microphotographs of the morphological structures of the puparia are included. Differences with close species are discussed.